DIGITALISASI SISTEM KEUANGAN UMKM: PELATIHAN PRAKTIS PENCATATAN DAN PELAPORAN KEUANGAN DIGITAL UNTUK PELAKU USAHA SERAT AGEL DI DAERAH ISTIMEWA YOGYAKARTA - Ridwan, Muhamad; Pradana, Musthofa Galih; Nyamiati, Retno Dwi; Pinastawa, I Wayan Rangga; Arifuddin, Nurul Afifah; Adrezo, Muhammad; Maulana, Nurhuda (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The digitalization of financial management has become an essential requirement for micro, small, and medium enterprises (MSMEs) to ensure their sustainability and growth in the modern economic landscape. Nevertheless, a significant proportion of MSME actors continue to encounter difficulties in systematically preparing financial statements and recording business transactions. This community engagement initiative was designed to enhance digital financial literacy among MSME artisans engaged in agel fiber crafts in the Sentolo area, Kulon Progo Regency, Special Region of Yogyakarta. The activity employed an interactive training method with a hands-on, practical approach, incorporating both the introduction and application of the SIAPIK platform, a digital tool aimed at facilitating transaction recording and the preparation of financial reports. The results of this activity demonstrate an improvement in participants' understanding of managing business finances through digital platforms. Additionally, participants also experienced an increase in motivation to implement technology-based financial recording. These findings also indicate their initial readiness to adopt digital transformation within their business environments.